Characterization of the interaction between rat pyruvate dehydrogenase kinase 4 and adp - Khoza, Thandeka (My University, 2009)
The primary role of pyruvate dehydrogenase kinase (PDK) is to regulate the activity of pyruvate dehydrogenase complex (PDC) with respect to the metabolic clearance of glucose via a phosphorylation mechanism. Therefore, inhibition of PDK is predicted to be important in the treatment of diabetes. ADP binds to the active site of PDK; and has been shown to inhibit PDK activity. This research work was aimed at studying one of the isoforms of PDK, specifically the rodent form, PDK4 (rPDK4) and further elucidating the binding properties of ADP to rPDK4. The hypothetical structure of rPDK4 was modelled based on the coordinates of the published rPDK2 structure. The overall structural topology of rPDK2 appears to be preserved in rPDK4. Further, the ADP binding site between rPDK2 and rPDK4 was conserved at both the primary and tertiary level, and this suggested the mechanism of ADP binding to rPDK2 would be similar to that of rPDK4. A histidine tagged-rPDK4 protein was expressed and purified using affinity and gel filtration chromatography. It was determined to be a homodimer (97 kDa) comprising two identical subunits. The rPDK4 protein was further identified to be rPDK4 using Western blot analysis as it reacted positively with an anti-rPDK4 monoclonal antibody. The purified rPDK4 protein contained kinase activity since it was able to undergo autophosphorylation and subsequently phosphorylate a peptide that contained the E1a subunit sites that are known to be phosphorylated by PDKs. The structure of rPDK4 protein was also characterised using circular dichroism and fluorescence spectroscopy.The spectroscopic data of rPDK4 was consistent with published data on the structure of rPDK4. The binding of ADP and ATP was studied using fluorescence quenching as both these ligands quench the intrinsic tryptophan fluorescence of rPDK4. The dissociation constant (Kd) values for ADP and ATP were determined to be 37 and 17.4 μM, respectively. The moderate affinity binding of ATP will greatly favour the exchange of ADP for a molecule of ATP to prevent PDK inhibition by ADP.